2016
DOI: 10.1111/jori.12159
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Buy‐Ins and Buy‐Outs

Abstract: Pension buy‐ins and buy‐outs have become an important aspect of managing pension risk in recent years. As a step toward understanding these pension de‐risking instruments, we develop models for pricing investment risk and longevity risk embedded in pension buy‐ins and buy‐outs. We also bring a contingent‐claims framework to price credit risk of buy‐in bulk annuities. Overall, our model can be used to assess the pricing of investment, longevity, and credit risks being transferred in pension buy‐in and buy‐out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…This assumption is made because the pricing formula in (3.3) does not address what happens to the remaining assets after all pensioners are deceased. Lin et al (2017), for instance, addressed this in relation to investment risk premium calculation.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is made because the pricing formula in (3.3) does not address what happens to the remaining assets after all pensioners are deceased. Lin et al (2017), for instance, addressed this in relation to investment risk premium calculation.…”
Section: Modelmentioning
confidence: 99%
“…We believe that this investment strategy is not unrealistic for annuity insurers who tend to have a rather low exposure to equity risk and prefer fixed income securities (FitchRatings, 2011). In their study, Lin et al (2017) have also suggested values for the correlation between the three asset classes and parameter values for the price dynamics. Adopting those parameter values, we find that the price process of the portfolio can be modelled as in (2.13) and (3.2) with the parameter values given in Table 4.…”
Section: Modelmentioning
confidence: 99%
“…Female directors may also balance the costs and benefits of such decisions. Given that Lin, Shi and Arik (2017) suggest that implementing pension BIOs may constrain firms facing poor financial conditions, female directors may worry about the significant costs of such actions. However, since female directors appear to be less traditional (Adams and Funk, 2012) and more risk‐averse (Croson and Gneezy, 2009) than male directors, they may be more likely to use new financial tools to help reduce firms’ pension obligations.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…• Design and pricing of longevity bonds and other longevity-linked products (e.g. Blake et al, 2006aBlake et al, , 2006bBlake et al, , 2014Bauer, 2006;Bauer & Ruß, 2006;Antolin & Bloomestein, 2007;Bauer & Kramer, 2007Barbarin, 2008;Bauer et al, 2010b;Chen & Cummins, 2010;Kogure & Kurachi, 2010;Bravo, 2011;Dowd et al, 2011a;Mayhew & Smith, 2011;Zhou et al, 2011Zhou et al, , 2013Chen et al, 2013;Shen & Siu, 2013;Denuit et al, 2015;Hunt & Blake, 2015;Milevsky & Salisbury, 2015;Yang et al, 2015;Wang & Li, 2016;Chen et al, 2017;Lin et al, 2017b ;Leung et al, 2018;MacMinn & Richter, 2018;. • Design and pricing of longevity-linked derivatives (e.g.…”
Section: • Landg Executed Buy-ins With the Pearson Pension Plan (£500m mentioning
confidence: 99%